2008
DOI: 10.4049/jimmunol.181.12.8226
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric Acid Transporter 1 Negatively Regulates T Cell-Mediated Immune Responses and Ameliorates Autoimmune Inflammation in the CNS

Abstract: γ-aminobutyric acid (GABA) is the major inhibitory neurotransmitter of the CNS, and GABA transporter 1 (GAT-1) is critical in maintaining a GABA reservoir and associated functions. The wide expression of GAT-1 in the CNS prompted us to explore its role in neuroimmunological disorders. In mice induced with experimental autoimmune encephalomyelitis (EAE), the animal model of multiple sclerosis, we found that the expression levels of GAT-1 mRNA and protein in spinal cord were greatly suppressed as compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 49 publications
5
44
0
Order By: Relevance
“…Our previous study has demonstrated that after Ag triggered T cell activation, GAT-1 expression is up-regulated (4). In this project, we found that PKC activation in T cells can also promote GAT-1 expression.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Our previous study has demonstrated that after Ag triggered T cell activation, GAT-1 expression is up-regulated (4). In this project, we found that PKC activation in T cells can also promote GAT-1 expression.…”
Section: Discussionsupporting
confidence: 51%
“…Neurotransmitters, together with their receptors and transporters, bridge the activity between nervous system and immune system (1,4). Studies of transgenic mice or of agonist/antagonist administration have established critical functions of neurotransmitters and associated molecules in regulating T cell responses (1,4,23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations